An In-depth Analysis of the Adverse Effects of Ionizing Radiation Exposure on Cardiac Catheterization Staffs - Alvandi, Maryam; Javid, Roozbeh N.; Shaghaghi, Zahra; Farzipour, Soghra; Nosrati, Sahar (Current Radiopharmaceuticals, 2024)
Diagnostic and interventional angiograms are instrumental in the multidisciplinary approach to CAD management, enabling accurate diagnosis and effective targeted treatments that significantly enhance patient care and cardiovascular outcomes. However, cath lab staff, including interventional cardiologists, is consistently exposed to ionizing radiation, which poses inherent health risks. Radiation exposure in the cath lab primarily results from the use of fluoroscopy and cineangiography during diagnostic and interventional procedures. Understanding these risks and implementing effective radiation protection measurements are imperative to ensure the well-being of healthcare professionals while delivering high-quality cardiac care. Prolonged and repeated exposure can lead to both deterministic and stochastic effects. Deterministic effects, such as skin erythema and tissue damage, are more likely to occur at high radiation doses. Interventional cardiologists and staff may experience these effects when safety measures are not rigorously followed. In fact, while ionizing radiation is essential in the practice of radiation cardiology ward, cath lab staff faces inherent risks from radiation exposure. Stochastic effects, on the other hand, are characterized by a probabilistic relationship between radiation exposure and the likelihood of harm. These effects include the increased risk of cancer, particularly for those with long-term exposure. Interventional cardiologists, due to their frequent presence in the cath lab, face a higher lifetime cumulative radiation dose, potentially elevating their cancer risk. Protective measures, including the use of lead aprons, thyroid shields, and radiation monitoring devices, play a crucial role in reducing radiation exposure for cath lab personnel. Adherence to strict dose optimization protocols, such as minimizing fluoroscopy time and maximizing distance from the radiation source, is also essential in mitigating these risks. Ongoing research and advancements in radiation safety technology are essential in further for minimizing the adverse effects of ionizing radiation in the cath lab.
Keywords: adverse effects